Can Wolbachia (Rickettsiaceae) explain female-biased sex ratios in mountain pine beetles (Coleoptera: Curculionidae)?. Issue 6 (20th January 2015) - Lachowsky, Leanna E.; Lalonde, Robert G.; Reid, Mary L.
Abstract: Wolbachia Hertig (Rickettsiales: Rickettsiaceae) is a genus of endosymbionts that are widespread in insects and can have important implications on population dynamics through cytoplasmic incompatibility or sex-ratio distortion. We considered Wolbachia as a possible explanation for female-biased sex ratios often observed in mountain pine beetle populations, Dendroctonus ponderosae Hopkins (Coleoptera: Curculionidae: Scolytinae), a major pest species in western Canada whose most recent outbreak and range expansion has killed many millions of mature lodgepole pine, Pinus contorta var. latifolia Engelmann (Pinaceae). We used wsp primers to screen for Wolbachia in 10 mountain pine beetle populations with varying degrees of female bias in southeast British Columbia and southwest Alberta, Canada. We found no evidence of Wolbachia in these populations and suggest that other factors may explain the sex-ratio bias. Résumé: Wolbachia Hertig (Rickettsiales: Rickettsiaceae) est un genre d'endosymbiontes répandus chez les insectes et pouvant avoir des conséquences importantes sur la dynamique des populations par le biais de l'incompatibilité cytoplasmique ou distorsion du rapport des sexes. Nous avons considéré Wolbachia comme une explication possible des rapports de sexe biaisés vers les femelles souvent observés dans les populations de dendroctones du pin ponderosa, Dendroctonus ponderosae Hopkins (Coleoptera: Curculionidae: Scolytinae), une des principales espèces de ravageurs dans l'ouest du Canada dont la plus récente éclosion et l'expansion de la distribution ont tué des millions de pins tordus matures, Pinus contorta var. latifolia Engelmann (Pinaceae). Nous avons utilisé des amorces wsp pour le dépistage de la bactérie Wolbachia dans 10 populations du dendroctone du pin ponderosa avec une gamme de biais du rapport des sexes dans le sud-est de la Colombie-Britannique et le sud-ouest de l'Alberta, Canada. Nous n'avons trouvé aucune preuve de Wolbachia dans ces populations et nous suggérons que d'autres facteurs peuvent expliquer le biais du rapport des sexes.